LITERATURE REVIEW : PENGARUH AEROBIC EXERCISE DAN WEIGH TRAINING AEROBIC Terhadap Indeks Massa Tubuh (IMT) Pada Calon Jamaah Haji - Fajar Nur Alamsyah (2020)
Background : Indonesia is adhering to the largest Islam in the world, especially in the implementation of the Hajj, Hajj in Indonesia is mostly done by adults and the elderly, along with aging there is an aging process and deterioration of endurance functions such as pulmonary heart, flexibility, muscles, balance, then the index body mass (imt), and can affect physical activity that is lifting goods, self, sitting, running and jumping therefore physical fitness can be improved by aerobic training and weight training. This study aims : to investigate the effect of aerobic exercise and aerobic weight training on body mass index (IMT) on prospective pilgrims. Method : this research uses literature review or literature review, Google Scholar review, Research Gat, Elsevier, PubMed, Science Direct using 2012-2020 time keywords, with traditional rivie literature design, Results: After 13 literatures have been selected and analyze the results found by using inclusion criteria and quality assessment methodology with Scimago Journal & Coutry Rank (SJR). Conclusion : after the literature has been done with the results that arobic exercise and weight training can affect the Body Mass Index (BMI) in the elderly and prospective pilgrims both men and women of course by using the principles of proper training.